The FveFT2 florigen/FveTFL1 antiflorigen balance is critical for the control of seasonal flowering in strawberry while FveFT3 modulates axillary meristem fate and yield. Issue 1 (16th July 2021) - Gaston, Amèlia; Potier, Aline; Alonso, Marie; Sabbadini, Silvia; Delmas, Frédéric; Tenreira, Tracey; Cochetel, Noé; Labadie, Marc; Prévost, Pierre; Folta, Kevin M.; Mezzetti, Bruno; Hernould, Michel; et al.
Summary: Plant architecture is central in determining crop yield. In the short‐day species strawberry, a crop vegetatively propagated by daughter‐plants produced by stolons, fruit yield is further dependent on the trade‐off between sexual reproduction (fruits) and asexual reproduction (daughter‐plants). Both are largely dependent on meristem identity, which establishes the development of branches, stolons and inflorescences. Floral initiation and plant architecture are modulated by the balance between two related proteins, FLOWERING LOCUS T (FT) and TERMINAL FLOWER 1 (TFL1). We explored in woodland strawberry the role of the uncharacterised FveFT2 and FveFT3 genes and of the floral repressor FveTFL1 through gene expression analyses, grafting and genetic transformation (overexpression and gene editing). We demonstrate the unusual properties of these genes. FveFT2 is a nonphotoperiodic florigen permitting short‐day (SD) flowering and FveTFL1 is the long‐hypothesised long‐day systemic antiflorigen that contributes, together with FveFT2, to the photoperiodic regulation of flowering. We additionally show that FveFT3 is not a florigen but promotes plant branching when overexpressed, that is likely to be through changing axillary meristem fate, therefore resulting in a 3.5‐fold increase in fruit yield at the expense of stolons. We show that our findings can be translated into improvement of cultivated strawberry in which FveFT2 overexpression significantly accelerates flowering.